2014
DOI: 10.1088/0256-307x/31/7/074206
|View full text |Cite
|
Sign up to set email alerts
|

An 880-nm Laser-Diode End-Pumped Nd:YVO 4 Slab Laser with a Hybrid Resonator

Abstract: We present an experimental study of a continuous-wave Nd:YVO4 laser diode-pumped directly in band at 880 nm. By using a compact positive confocal unstable-stable hybrid resonator, a maximal laser output of 170 W at 1064 nm is realized. The slope efficiency and optical-to-optical efficiency are 56.7% and 51.3%, respectively. The 𝑀 2 factors in the unstable direction and in the stable direction they are 1.9 and 1.3, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This will facilitate the miniaturization and high efficiency of solid state lasers. [37,38] 074205-2 According to the absorption spectra, the re-absorption effect is very serious at the wavelength between 900 nm to 1100 nm, so the excited wavelength was settled at 896 nm. The strongest emission peak (979 nm) corresponds to the zero-phonon line of Yb 3+ ion.…”
Section: Resultsmentioning
confidence: 99%
“…This will facilitate the miniaturization and high efficiency of solid state lasers. [37,38] 074205-2 According to the absorption spectra, the re-absorption effect is very serious at the wavelength between 900 nm to 1100 nm, so the excited wavelength was settled at 896 nm. The strongest emission peak (979 nm) corresponds to the zero-phonon line of Yb 3+ ion.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past twenty years, it has been demonstrated that thermal effects can be efficiently reduced by using composite laser crystals [12][13][14] and in-band pumping. [15][16][17][18] In 2010, we realized an efficient cw self-frequency Raman generation in a composite YVO 4 /Nd:YVO 4 /YVO 4 crystal. The Raman threshold was measured at 2.2 W of the traditional 808 nm diode laser (LD) pump.…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, we reported a 170 W 1064 nm output laser with the size of the crystal 22 mm × 12 mm × 1 mm. The M 2 factors were 1.9 and 1.3 in the unstable direction and in the stable direction, respectively [13]. In 2014, Liu Xu et al obtained a 340 W 1064 nm output laser with the double-end-pumped at 880 nm.…”
Section: Introductionmentioning
confidence: 99%